Investigation of functionally graded skew sandwich plates with geometrical deformations under hygro-thermo-mechanical loading - Khanke, Venushree S.; Tande, S.N. (Journal of Structural Engineering, 2024)
This study aims to carry out investigation of functionally graded skew sandwich plates with geometrical deformations under hygro-thermo-mechanical loading. It is performed using Higher Order Zigzag Theory (HOZT) and dimensionless deflections and stresses are obtained. Using HOZT, the criteria of continuous transverse shear stress at inter-laminar junctions and zero at the top and bottom surface of the plate is fulfilled. It thus eliminates the requirement of factor for shear correction. The material properties follow the power law variation and are dependent on temperature and moisture conditions. The temperature distribution is assumed to be linear and moisture distribution is assumed to be constant in the study. A 9-noded finite element with 11 dofs at each node is used for discretization of the plate. The influence of governing system components such as aspect ratio (a/h), volume fraction index (n), skew angle, boundary conditions, geometrical deformation types such as sine, global and local type and deformation amplitudes (ζ0) on dimensionless displacement and stresses is studied. The outcomes from this study are confirmed with those from the previous studies to authenticate the present formulation. New findings are put forth which can be used as reference for future studies in the similar field.